A ditadura militar no Espírito Santo: o consentimento por meio do jornal A Gazeta (1971-1975) - Santos, Davi Elias Rangel (2019)
This work intends to analyze the construction of a "positive memory" about the Military Dictatorship in Espírito Santo, through the newspaper A Gazeta during the government of Arthur Carlos Gerhardt Santos (1971-1975). For this purpose we will use the theoretical perspective on consent to try to understand the participation of sectors of civil society during this authoritarian political regime. Therefore, it is important to understand the political, social and economic context of the period known as "Economic Miracle"; specifically, the economic project of conservative modernization of the then military president Emílio Gastarrazu Médici (1969-1974); and how, in his government, censorship and political propaganda were used, which dictated the tone of the Communist practices of the Dictatorship with the citizens. It is in this repressive politico-social context that we seek to capture the presence of two competing memories: that of "triumph" and that of "trauma." In order to do so, a historiographical reflection on the contribution of the official Capixaba press (the newspaper A Gazeta) was necessary in the elaboration of this "positive" memory, through documental analysis of the printed matter, of which is the object and source, simultaneously of this work, and which are available in the State Public Archive and other corresponding collections. Thus, we will use the methodological approach of the German philosopher Jurgen Habermas and his concept on the Public Sphere, where he analyzes the performance of the press in the public space, as a body of mediation between the constituted government; and the French historian Roger Chartier, who develops the concept of social representation based on the practices and representations that shape society's way of thinking and acting in a particular historical context. Therefore, the paths of consensus and consent pursued by the military dictatorship (1964-1985) in Espírito Santo, whose mechanisms have been active in the past, echo in the present time indicating the silent conflicts between memories, in view of the complex relationship of society with the dictatorial regime that need to be revealed.